A human security perspective to human trafficking from Ethiopia to Saudi Arabia: the case of Atsbi Wenberta woreda in Tigray region. (2nd September 2022) - Kiros, Gebreslassie; Zeru, Mehari
ABSTRACT: This article studied human trafficking and associated threats exacerbating insecurity of victims, families and the community in Atsbi Wenberta woreda. Besides, it examined the response to the problem. Subsequently, this article underlined applying a human security perspective is required to address the root cause and risks of human trafficking.